Lightning activity in Brazilian thunderstorms during TROCCINOX: implications for NOx production - Huntrieser, H.; Schumann, U.; Schlager, H.; Hoeller, H.; Giez, A.; Betz, H. -D.; Brunner, D.; Forster, C.; Pinto, O.; Calheiros, R. [UNESP] (Copernicus Gesellschaft Mbh, 2008)
During the TROCCINOX field experiment in January and February 2005, the contribution of lightning-induced nitrogen oxides (LNOx) from tropical and subtropical thunderstorms in Southern Brazil was investigated. Airborne trace gas measurements (NO, NOy, CO and O-3) were performed up to 12.5 km with the German research aircraft Falcon. During anvil penetrations in selected tropical and subtropical thunderstorms of 4 and 18 February, NOx mixing ratios were on average enhanced by 0.7-1.2 and 0.2-0.8 nmol mol(-1) totally, respectively. The relative contributions of boundary layer NOx (BL-NOx) and LNOx to anvil-NOx were derived from the NOx-CO correlations. on average similar to 80-90% of the anvil-NOx was attributed to LNOx. A Lightning Location Network (LINET) was set up to monitor the local distribution of cloud-to-ground (CG) and intra-cloud (IC) radiation sources (here called 'strokes') and compared with lightning data from the operational Brazilian network RINDAT (Rede Integrada Nacional de Deteccao de Descargas Atmosfericas). The horizontal LNOx mass flux out of the anvil was determined from the mean LNOx mixing ratio, the horizontal outflow velocity and the size of the vertical cross-section of the anvil, and related to the number of strokes contributing to LNOx. The values of these parameters were derived from the airborne measurements, from lightning and radar observations, and from a trajectory analysis. The amount of LNOx produced per LINET stroke depending on measured peak current was determined. The results were scaled up with the Lightning Imaging Sensor (LIS) flash rate (44 flashes s(-1)) to obtain an estimate of the global LNOx production rate. The final results gave similar to 1 and similar to 2-3 kg(N) per LIS flash based on measurements in three tropical and one subtropical Brazilian thunderstorms, respectively, suggesting that tropical flashes may be less productive than subtropical ones. The equivalent mean annual global LNOx nitrogen mass production rate was estimated to be 1.6 and 3.1 Tg a(-1), respectively. By use of LINET observations in Germany in July 2005, a comparison with the lightning activity in mid-latitude thunderstorms was also performed. In general, the same frequency distribution of stroke peak currents as for tropical thunderstorms over Brazil was found. The different LNOx production rates per stroke in tropical thunderstorms compared with subtropical and mid-latitude thunderstorms seem to be related to the different stroke lengths (inferred from comparison with laboratory data and observed lengths). In comparison, the impact of other lightning parameters as stroke peak current and stroke release height was assessed to be minor. The results from TROCCINOX suggest that the different vertical wind shear may be responsible for the different stroke lengths.